Effect of Work Ethics and The Work Environment on Performance of Employees of PT. Berlian Indah Abadi Nusantara Surabaya - Firmansyah Anggarda Dewantara; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to see the work ethic and work environment variables on the performance of the employees of PT Berlian Indah Nusantara Abadi Surabaya, partially or simultaneously. The method used in this method is quantitative and the data obtained from the distribution of questionnaires given to 57 employees, consisting of men mean 30 people while 27 women. Then for the analysis technique using multiple linear regression analysis processed using the SPSS version 21.00 program. From the research results, work ethics have a positive and significant effect on employee performance. Meanwhile, the work environment has a negative and significant effect on the work environment.